Tailoring cathode structure of catalyst coated membranes for performance enhancement in direct methanol fuel cells. (14th December 2016) - Mehmood, Asad; An, Myunggi; Ha, Heung Yong
Abstract: In this study, we demonstrate how the formulation of colloidal catalyst ink and fabrication conditions affect the cathode microstructure of catalyst coated membranes (CCMs) prepared via decal technique. The CCMs based on conventional and high concentration cathode inks are compared in a direct methanol fuel cell (DMFC). It is found that the cathode catalyst layer made with a high concentration ink possesses superior porosity, leading to an improved DMFC performance. The temperature of roll-press used for preparing CCM is varied ranging from 170 to 210 °C in order to determine the optimal fabrication conditions for high concentration ink-based cathode. The CCM hot-pressed at 200 °C (advanced CCM) retains a significantly higher pore volume and outperforms the conventional CCM by delivering an excellent DMFC performance with a maximum power density of 155 mW cm −2, which is 20% higher than that of the conventional CCM. Graphical abstract: Highlights: Catalyst-coated membranes (CCMs) are fabricated via a decal transfer technique. Cathode porosity is improved by increasing the concentration of colloidal ink. Hot-pressing temperature is re-adjusted with the alteration of ink composition. Advanced CCMs made with concentrated inks substantially improve DMFC performance.